Electrical Conduction mechanism in Copper-Poly(Vinyl Alchol) Composites - Mosaad, M.M. (Asian Journal of Chemistry, 2010)
Electrical conduction of pure poly(vinyl alcohol) (PVA) and copper poly(vinyl alcohol) composites (Cu-PVA) is studied as function of voltage and temperature. From log I - log V relations, it is found that we cannot explain the conduction mechanism on the basis of space-charge limited current. The values of Schottky field lowering constant βSR was calculated and compared with βexp which was calculated from the slope of In I - V½. It is found that at low temperature for pure sample the conduction may be due to a combination of electronic and ionic parts. But for other samples a quite large difference between βPF and βexp is observed. We conclude that the In I - V½ study of these composites samples does not help us in knowing the exact case of the conduction mechanism of these samples.